Marjolin’s ulcer – epidemiology and the pattern of care: Experience from a tertiary cancer care center - Anjan Bera,; Shatarupa Dutta,; Chandrima Banerjee,; Asmita Dasgupta,; Srikrishna Mandal,; Saptarshi Banerjee, (Asian Journal of Medical Sciences, 2023)
Background: Marjolin’s ulcer (MU) reflects the malignant transformation of scar tissue or chronic inflammatory skin lesions. Due to the low incidence, only a few case reports and case series were reported in the literature to date. Aims and Objectives: In our retrospective analysis, we report our experience regarding MU over the past 16 years with a significant range of latent period, histology, and as well as underlying skin conditions, from Kolkata, India. Materials and Methods: This was a single institutional retrospective study carried out in the department of radiotherapy at the tertiary cancer, Kolkata. We focus mainly on data pertaining to the type of injury, the time gap between the initial injury and development of MU, histology, clinical stage, and treatment received, along with demographic details. Results: A total of 39 patients with histopathologically proved MUs were included according to the inclusion and exclusion criteria. The median age of patients at the time of development of MU was 52 years and with a range of 32–71 years. Out of 39 patients who participated in this study, 29 were male (74%) and ten were female (26%), 31 patients have localized disease (80%) and eight patients have metastatic disease (20%). The most common histology is squamous cell carcinoma and the least common histology was spindle cell sarcoma. The majority of the patients were treated with curative intention and a small proportion of patients were offered palliative therapy. Conclusion: Ulcers refractory to basic wound care, chronic in nature, and recent change of character of long-standing scar or wound, diagnosis of MU should be ruled out by biopsy. The management of MU should be supervised by a multidisciplinary tumor board and in the areas of epidemiology and treatment, more research is needed.